Digital transformation and its impact on labour productivity: A multi-sector perspective - Elisabeth Falck; Oke Röhe; Johannes Strobel (Deutsche Bundesbank, 2024)
In recent years, there has been a controversial debate on how the rapid diffusion of digital technologies affects labour productivity in advanced economies. Using a multi-sector dynamic general equilibrium model, we show that cumulative labour productivity growth in the United States, Germany and France over the period from 1996 to 2020 would have been about half as high without the efficiency gains from the sectors producing digital goods - despite their relatively small size in terms of gross value added. This is not only because TFP growth in the digital sectors is exceptionally high, but also because other sectors benefit from these efficiency improvements via production linkages.
Keywords: E17; E23; E24; O33; O41; O47; 330; dynamic general equilibrium model; sectoral linkages; production network; digitalisation